Myasthenia gravis: Diagnostic journey and therapeutic outcomes in patients followed at a Brazilian public tertiary center — A retrospective cohort study - Diego Silva Figueiredo; Alberto Rolim Muro Martinez; Anamarli Nucci; Marcondes Cavalcante França Junior (PLoS ONE, 2026)
Background Myasthenia gravis (MG) is a heterogeneous autoimmune disorder of the neuromuscular junction. Diagnosis and management remain challenging in real-world settings, particularly in public health systems. Data from resource-constrained countries are limited. This study aimed to characterize the epidemiological, clinical, and therapeutic profile of MG patients followed in a Brazilian public tertiary center, emphasizing diagnostic delay and treatment outcomes. Methods We conducted a retrospective single-center cohort study of 150 adult MG patients evaluated from 2024 to 2025. Clinical, immunological, therapeutic, and diagnostic-journey data were extracted from institutional electronic and paper medical records, and structured patient questionnaires, when available. Patients were classified as drug-responsive, corticosteroid-dependent, or drug-refractory using predefined operational criteria informed by international consensus guidance. Between-group comparisons used parametric or nonparametric tests, and categorical variables were analyzed with chi-square, Fisher’s exact, or Monte Carlo permutation chi-square tests, as appropriate. Results The cohort had female predominance (65.3%), with a median age at onset 35.5 years (IQR 25–48). Among those tested, most were AChR antibody–positive (67.6%) and presented generalized MG (93.3%). Median diagnostic delay was 11 months, and 47.3% had delays ≥1 year. Refractory MG occurred in 14% and corticosteroid dependence in 10.6%. Documented myasthenic crisis and impending crisis occurred in 25.2% (35/139) and 27.3% (38/139), respectively; documented myasthenic crisis was more frequent in refractory than in drug-responsive patients (45.0% vs 21.0%). Treatment-related adverse events were documented in 47.5% (67/141); among affected patients, the most common were hyperglycemia (37.3%), osteoporosis/osteopenia (17.9%), and weight gain (16.4%). Conclusions MG patients followed at this Brazilian public tertiary center showed clinical profiles broadly comparable to those reported in international cohorts, but diagnostic delays were frequent. The frequencies of refractory disease and corticosteroid dependence highlight the need for earlier recognition, specialized management, optimized steroid-sparing strategies, and improved access to comprehensive MG care.